Designing LEEF (Learning English Easy and Fun) as Learning Media for the Seventh Grade of Junior High School - Ma'arif, Iin Baroroh; Bahtiar, Yuyun; Muthoharoh, Muthoharoh (FOSTER: Journal of English Language Teaching, 2021)
This research aims at designing a learning media which named LEEF (Learning English Easy and Fun) as English learning media for seventh grade students of Junior High School. This learning media consists of some materials and exercises which is appropriate and feasible to be studied for students. All materials in this media are based on junior high school syllabus of K13 curriculum. The research method used in this research is Research and Development. This development used ADDIE model which have several steps, those are; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The result of this research shows that from the media validation result got 4.00 score it was in “fair and worth to use” category, and the material validation got 3.86 score. The students’ responses of try out result score 4.26 were in “fair and worth to use” category. By having those result, this LEEF (Learning English Easy and Fun) is feasible to be used as a learning media for seventh grade students of junior high school. Furthermore this research can be used as reference to other researchers in developing English learning media in different level of students.